2019
DOI: 10.3389/fnins.2019.00617
|View full text |Cite
|
Sign up to set email alerts
|

Brain Molecular Connectivity in Neurodegenerative Diseases: Recent Advances and New Perspectives Using Positron Emission Tomography

Abstract: Positron emission tomography (PET) represents a unique molecular tool to get in vivo access to a wide spectrum of biological and neuropathological processes, of crucial relevance for neurodegenerative conditions. Although most PET findings are based on massive univariate approaches, in the last decade the increasing interest in multivariate methods has paved the way to the assessment of unexplored cerebral features, spanning from resting state brain networks to whole-brain connectome properties. Currently, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 127 publications
(215 reference statements)
2
68
0
Order By: Relevance
“…Building on the core principle that brain regions whose metabolism is correlated at rest are functionally interconnected (Horwitz, Duara, & Rapoport, ), we applied a voxelwise seed‐based interregional correlation analysis (Lee et al, ). This method was previously validated for [18F]FDG–PET data (Horwitz et al, ; Lee et al, ) and allows to derive resting‐state metabolic networks starting from proper seed regions (Ballarini et al, ; Iaccarino et al, ; Perani et al, ; Sala et al, ; Tomasi et al, ; see also Sala & Perani, for a recent review).…”
Section: Methodsmentioning
confidence: 99%
“…Building on the core principle that brain regions whose metabolism is correlated at rest are functionally interconnected (Horwitz, Duara, & Rapoport, ), we applied a voxelwise seed‐based interregional correlation analysis (Lee et al, ). This method was previously validated for [18F]FDG–PET data (Horwitz et al, ; Lee et al, ) and allows to derive resting‐state metabolic networks starting from proper seed regions (Ballarini et al, ; Iaccarino et al, ; Perani et al, ; Sala et al, ; Tomasi et al, ; see also Sala & Perani, for a recent review).…”
Section: Methodsmentioning
confidence: 99%
“…In EOAD, [ 18 F]-FDG PET imaging studies showed, at a comparable level of clinical severity, a greater brain hypometabolism than in LOAD [5,[23][24][25] and an extension of the hypometabolism in frontal and occipital regions in atypical presentations [26,27]. More recently, [ 18 F]-FDG PET measures have been used for the evaluation of brain metabolic connectivity [28]. [ 18 F]-FDG PET brain glucose consumption reflects neuronal communication signaling, both locally and between distant brain regions, and is closely associated with functional connectivity [29].…”
Section: Introductionmentioning
confidence: 99%
“…As non-invasive technique, [ 18 F]FDG PET has also been used to monitor the regional effects of potential CNS drugs and/or pharmacological challenges with repeated scans [ 3 6 ]. More recently, [ 18 F]FDG brain PET was also applied to unravel brain networks in healthy and diseased brains [ 7 ]. Many quantification approaches exist to determine brain glucose metabolism, hence questioning the accuracy of the different [ 18 F]FDG PET quantification methods.…”
Section: Introductionmentioning
confidence: 99%